C# basics for absolute beginners in C# and .NET. (Packt Publishing, 2022)
Learn the fundamentals of C# .NET programming from the ground up About This Video Build a solid foundation on the basics of C# programming language and coding constructs Lots of demos showing how to use newly learned C# coding constructs Each lesson in this course is bite-sized and easy to finish In Detail C# is a simple, yet modern Object-Oriented Programming language developed by Microsoft within its .Net initiative. This comprehensive course will help you understand the fundamentals of coding with C# in .NET environment. In this course, you will start from the basics and cover the basics of the C# programming language right from setting up the .NET development environment. Then move to an overview of .NET, C# coding concepts such as variables, operators, selection, and iterative statements, debugging C# programs, and more. Each concept is explained with the help of practical demonstrations showing how to use newly learned C# coding constructs. This is a beginner-level course, and some programming experience is suggested but not required. By the end of this course, you will have a solid foundation in the basics of C# programming language and coding constructs, gain more confidence to learn advanced C# programming concepts, and will be ready to begin your career as a C# .NET programmer. Who this book is for This course is designed for absolute beginners, who are completely new to C# and .NET. Programmers who have experience in a language other than C# can also opt for this course. No prior C# or .NET coding experience is required.